2023
DOI: 10.1111/modl.12880
|View full text |Cite
|
Sign up to set email alerts
|

Out‐of‐classroom L2 vocabulary acquisition: The effects of digital activities and school vocabulary

Batia Laufer,
Esther Emma Vaisman

Abstract: Extramural exposure, through activities such as watching TV, gaming, networking, and online reading, has become an important source of vocabulary acquisition in English as a foreign language, particularly when learners’ first language (L1) has many cognates with English. Our study examined extramural vocabulary acquisition of 10th‐grade L1 speakers of noncognate languages over one school year and explored the effects of digital activities and initial lexical knowledge of the participants on their vocabulary ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 66 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…However, the results of these studies regarding the influence of distinct kinds of extramural English activities on learners' vocabulary size have been somewhat inconsistent and contradictory (Kaatari et al, 2023). Some studies have observed a positive association between viewing non-subtitled TV programs and learners' vocabulary knowledge (Peters, 2018;Tam & Reynolds, 2022), whereas others have detected a stronger correlation between online reading and vocabulary size (Laufer & Vaisman, 2023). Other researchers (De Wilde et al, 2020), however, have found that digital gameplay and the use of social media significantly contribute more to vocabulary development than other types of extracurricular activities.…”
Section: Vocabulary Growth Through Extramural Englishmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the results of these studies regarding the influence of distinct kinds of extramural English activities on learners' vocabulary size have been somewhat inconsistent and contradictory (Kaatari et al, 2023). Some studies have observed a positive association between viewing non-subtitled TV programs and learners' vocabulary knowledge (Peters, 2018;Tam & Reynolds, 2022), whereas others have detected a stronger correlation between online reading and vocabulary size (Laufer & Vaisman, 2023). Other researchers (De Wilde et al, 2020), however, have found that digital gameplay and the use of social media significantly contribute more to vocabulary development than other types of extracurricular activities.…”
Section: Vocabulary Growth Through Extramural Englishmentioning
confidence: 99%
“…One main strand of research is concerned with the relationship between such activities and L2 vocabulary development, typically drawing on data collected through questionnaires and vocabulary size measures. Generally, a large body of studies has suggested a positive association between engagement in extracurricular activities and the L2 vocabulary learning of learners from various contexts (e.g., De Wilde & Eyckmans, 2017;Laufer & Vaisman, 2023;Lee, 2019;Rød & Calafato, 2023;Sundqvist & Wikström, 2015). However, the results of these studies regarding the influence of distinct kinds of extramural English activities on learners' vocabulary size have been somewhat inconsistent and contradictory (Kaatari et al, 2023).…”
Section: Vocabulary Growth Through Extramural Englishmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of researchers have conducted studies on learners' mastery of vocabulary issues all across the world. They discovered that many EFL learners still struggle to memorize vocabulary in school because they have less vocabulary learning techniques (Arndt & Woore, (2018); Feng & Webb, (2020); Laufer & Vaisman, (2023) ;Xia, (2018). Some students have difficulties remembering the definitions that has been given, which hinder the learning.…”
Section: Introductionmentioning
confidence: 99%